IMPLEMENTATION OF CHILD PROTECTION POLICIES IN INDONESIA - A COMPARISON STUDY OF THE EFFECTIVENESS OF CHILD PROTECTION INSTITUTIONS PERFORMANCE - Taufik Makarao; Quthub Al Faruqi (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2023)
The study considers the effectiveness of the performance of child protection institutions, namely The Ministry of Empowerment of Women and Child Protection (KPPPA), The Indonesian Child Protection Commission (KPAI), The Child Protection National Commissions (Komnas PA) and The Indonesian Children's Protection (LPAI) in an effort to optimize the implementation of child protection policies in Indonesia, based on individual institutions' positions, duties and functions, And comprehensive discussion on issues that impede the effectiveness of the implementation of child protection policies from individual institutions. Researchers use normative-study methods with a normative-normative juridical approach. The data source consists of the primary material of law, which is bill no. 23 of 2002 on child protection and other related legislation, a secondary legal ingredient of journals, articles, and other scientific items that have a bearing on the subject of researchers, non - law articles, encyclopedias and others. For further analysis and explanatory purposes to this study, using a comparative approach made by comparing one legal institution with another so that the differences and similarities in circumstances, circumstances, history and legal systems in each body were examined. Research shows that the ineffective implementation of child protection policies carried out by child protection agencies today is caused by a complex phenomenon of the implementation of child protection policies from various factors influencing them. From the beginning of fundamental issues that occur in communities which are closely related to the still less cultures and cultures of Indonesian law, the level of knowledge and understanding of society in a large way toward the content of legislation, generalized regulatory communication patterns, the brevity of governance between institutions, the lack of jobs and functions given by the law, the lack of budgets, The lack of a representative agency in the region, the poor political commitment of local governments, the sectarian ego between relevant agencies, the unprofessional law enforcement officers in the performance of their duties and authority, and the limitations to the means, infrastructure and facilities that each institution has in supporting law enforcement.